Effects of the quality of pre-consolidated materials on the mechanical properties and morphology of thermoplastic pultruded flat laminates. (November 2022) - Minchenkov, Kirill; Vedernikov, Alexander; Kuzminova, Yulia; Gusev, Sergey; Sulimov, Artem; Gulyaev, Artem; Kreslavskaya, Anastasia; Prosyanoy, Ilya; Xian, Guijun; Akhatov, Iskander; Safonov, Alexander
Abstract: Pre-consolidated tapes in thermoplastic pultrusion solve the problem of impregnating a reinforcement with high-viscosity thermoplastic resins. Thermoplastic glass fiber/polypropylene flat laminates (75 mm × 3.5 mm) were fabricated using pre-consolidated tapes from different manufacturers: pre-consolidated tapes by the ApATeCh-Tape Company (Russia) and pre-consolidated sheets by the Zhongji Company (China). In spite of the equal reinforcement volume fraction (38%), the laminates fabricated from the pre-consolidated sheets exhibited higher compressive, tensile, and flexural strengths than those made from the pre-consolidated tapes, differing by 27.1%, 27.3%, and 19.8%, respectively. The observed difference between the strength characteristics of the studied flat laminates was explained by the presence of unimpregnated regions in the fiber bundles and by matrix cracks in the pre-consolidated tapes, absent in the pre-consolidated sheets, as revealed by the scanning electron microscopy analysis. Such defects cannot be corrected during the pultrusion process, resulting in the formation of matrix cracks and debonding, impairing the mechanical performance of the produced pultruded laminates. Pre-consolidated sheets enable pultrusion flat laminates with larger cross-sections, exhibiting better mechanical performance and surface roughness, compared with thermoplastic pultruded composites fabricated from pre-consolidated tapes described in the literature. Graphical abstract: Image 1 Highlights: Thermoplastic glass fiber/polypropylene pultruded flat laminates were fabricated using different pre-consolidated tapes. Laminates fabricated from tapes by Zhongji exhibited higher properties than those made from tapes by ApATeCh-Tape. The observed difference was explained by the presence of unimpregnated regions and by matrix cracks in the tapes.